2012
DOI: 10.1093/mp/sss039
|View full text |Cite
|
Sign up to set email alerts
|

Light-Regulated Stomatal Aperture in Arabidopsis

Abstract: The stomatal pores of plant leaves, situated in the epidermis and surrounded by a pair of guard cells, allow CO2 uptake for photosynthesis and water loss through transpiration. Blue light is one of the dominant environmental signals that control stomatal movements in leaves of plants in a natural environment. This blue light response is mediated by blue/UV A light-absorbing phototropins (phots) and cryptochromes (crys). Red/far-red light-absorbing phytochromes (phys) also play a role in the control of stomatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 68 publications
1
65
0
2
Order By: Relevance
“…Wang et al (2014a), in this issue, have undertaken such an approach using OnGuard models for V. faba and Arabidopsis (Chen et al, 2012a;Hills et al, 2012;Wang et al, 2012). OnGuard models incorporate all of our knowledge of molecular, biophysical, and kinetic characteristics of guard cell transport, Mal metabolism, and H + and Ca 2+ buffering, and they link this knowledge to stomatal aperture.…”
Section: Ion Transport Stomatal Response and Wuementioning
confidence: 99%
“…Wang et al (2014a), in this issue, have undertaken such an approach using OnGuard models for V. faba and Arabidopsis (Chen et al, 2012a;Hills et al, 2012;Wang et al, 2012). OnGuard models incorporate all of our knowledge of molecular, biophysical, and kinetic characteristics of guard cell transport, Mal metabolism, and H + and Ca 2+ buffering, and they link this knowledge to stomatal aperture.…”
Section: Ion Transport Stomatal Response and Wuementioning
confidence: 99%
“…10,11 ABA triggers a signaling network in guard cells that includes protein kinases and leads to activation of anion channels and the outward movement of anions, resulting in loss of turgor and reduction of the stomatal aperture. [12][13][14][15][16][17] Blue light triggers stomatal opening in most plants 18 by a signaling network that involves protein kinases and results in the phosphorylation and activation of the H C -ATPase in the plasma membrane of the guard cell. [19][20][21][22][23] Loss of H C leads to uptake of K C , increase in turgor, and increase of the stomatal aperture.…”
Section: Introductionmentioning
confidence: 99%
“…Stomatal movements are regulated by a variety of factors that stimulate opening and closure (Kim et al, 2010;Araújo et al, 2011;Chen et al, 2012). It has been reported that stomatal movement may be influenced by UV-B, and the response observed (opening or closure) is dependent on the fluence rate (Nogues et al, 1999;Jansen and Noort, 2000;Eisinger et al, 2003;He et al, 2005He et al, , 2013.…”
mentioning
confidence: 99%